Design and analysis a black box for used cooking oil filtration - Abdul Kadir, Hakim Naqiuddin (2021)
Used cooking oil (UCO) s oil that has been used for cooking or frying. UCO is commonly found in the food and beverage industry, as well as at home. Therefore, the main source for preparing food is cooking oil. Restaurants and kitchens will produce a lot of waste from cooking oil. However, improper disposal of waste from UCOs may have negative consequences such as clogged drains, foul odour production, and pollution. As a result, the project will create a filter box design to re-filter the UCO so that it can have a proper disposal method. This methodological study is based on the Quality Function Deployment (QFD) method, which includes customer surveys, Voice of Customers (VoC), and questionnaires to assess user needs to build a House of Quality (HoQ). The design process is then continued by developing design requirements. Next is the generation of a design containing a morphological chart. Finally, make a design selection using computer-aided design software that produces a visual prototype. The findings show that black boxes for used cooking oil refining realise customer needs.